Pengembangan Modul Interaktif Pembelajaran Biologi Berbasis Discovery Learning untuk Meningkatkan Keterampilan Berpikir Kreatif pada Materi Sistem Ekskresi di SMA - Zahraa Zalikha; Efrida Pima Sari Tambunan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to develop an interactive Biology module based on Discovery Learning on the Excretory System topic for eleventh-grade students and to evaluate its validity, practicality, and effectiveness in improving creative thinking skills. The method used was Research and Development (R&D) using the 4D model, involving 26 eleventh-grade students, expert validation sheets, teacher and student response questionnaires, and essay tests based on creative thinking indicators, with data analyzed using Likert scales, percentages, and N-Gain. The findings revealed that the developed module was highly valid, practical for classroom use, and capable of improving students' creative thinking skills. Conclusion, the Discovery Learning-based interactive module is feasible and effective as a learning resource for the excretory system topic and supports the development of creative thinking skills. Keywords: Creative Thinking Skills, Discovery Learning, Excretory System, Interactive Module